Analisis Nilai-Nilai Kearifan Lokal Program Sekolah Budaya Sebagai Penunjang Projek Profil Pelajar Pancasila dalam Kurikulum Merdeka di SDN Kaliwining 07 Rambipuji Jember - Surul, Rofiatus (Jurnal Kependidikan, 2024)
In Indonesia, the curriculum has changed several times in line with the change of ministers and the needs of students. Recently it has been intensified in relation to the independent curriculum initiated by the Ministry of Education and Culture. The Merdeka curriculum promotes a comfortable, happy and structured learning atmosphere for students and educators. To achieve the expected competencies in the implementation of the independent curriculum, a project was designed to strengthen the profile of Pancasila students as a curricular activity to support competency achievement in the learning process. To support the achievement of the competencies expected in the Pancasila student profile project, Kaliwining 07 State Elementary School implemented a cultural school program, where students while in the school environment were listened to by national and regional songs, as well as traditional games. The approach used in this research is a qualitative approach with a descriptive type. While the data collection technique uses three stages, namely observation, interviews, and documentation. The data analysis used is Miles and Huberman's interactive analysis, namely data reduction, data presentation and drawing conclusions. Test the validity of the data using source triangulation and technique triangulation. So as to produce research results that, the application of the cultural school program at SDN Kaliwining 07 Rambipuji Jember which grows and develops colors the quality of life in schools which also contributes to instilling local wisdom values. in the Pancasila student profile project, where students are expected to be able to understand and apply Pancasila values ​​in everyday life. One way to achieve this goal is to integrate local wisdom values ​​into learning activities in the school environment through the Cultural School program. Thus, students can understand that Pancasila is not just a concept or ideology, but also includes local wisdom values ​​that are part of the culture and character of the Indonesian nation